The Role of Fuel and Energy Sector in the Eurasian Economic Community Integration Process - Guliyev, Igbal A.; Mekhdiev, Elnur T. (International Journal of Energy Economics and Policy, 2017)
The article focuses on creation of the common energy space among the Customs Union and the Common Economic Space countries. We analyzes energy markets in Russia, Kazakhstan and Belarus, natural resources potential of these countries and their energy exports, as well as pays particular attention to the current oil and gas supplies regulation within the Customs Union. The main problems emphasized in the article are the common oil and gas market establishment, harmonization of the national energy legislation, effective transit potential use, development and adoption of common rules for the oil and gas industry access, removal of duties and establishment of common tariff policy. In conclusion, recommendations for development of Russia's Eurasian integration strategy are presented. Keywords: Energy, Eurasian integration, Common Economic Space. JEL Classification: F020